Mindfulness and engagement in COVID-19 preventive behavior - Haliwa, Ilana (Prev Med Rep, 2020)
The novel coronavirus disease 2019 (COVID-19) pandemic represents a significant risk to population health. Health organizations worldwide have recommended numerous preventive health behaviors to slow the spread of COVID-19. Yet, considerable variability exists in individual-level adherence to these recommendations. Mindfulness has been associated with greater engagement in health promotive behavior (e.g., physical activity, healthy eating), and may serve as an individual difference factor that encourages adherence. However, no study to date has examined the extent to which mindfulness is associated with preventive health behaviors during a global pandemic. The purpose of the present study was to assess the relations between mindfulness and recommended preventive health behaviors for COVID-19. A national U.S. sample (N = 353; M(age) = 41.47 years, range: 19–84; 50.2% female) completed an online survey via Amazon’s Mechanical Turk from April 3rd to 15th, 2020, including measures of mindfulness and frequency of avoiding touching one’s face, handwashing, disinfecting/cleaning frequently used surfaces, social distancing, and self-quarantining. Personality, health risk, and demographic factors were also assessed to test the unique association between mindfulness and preventive health behaviors. Mindfulness was significantly correlated with greater engagement in all of the COVID-19 preventive health behaviors. However, when accounting for demographics, health risk, and personality, mindfulness was only uniquely associated with engagement in social distancing. This research highlights mindfulness as an individual-level characteristic associated with engagement in COVID-19 preventive health behavior and may inform future prevention efforts aimed at improving adherence to recommendations for curbing the spread of infectious disease.